Penggunaan Metode Story Telling Guru Sekolah Minggu Dalam Pemahaman Alkitab Pada Anak usia 3-6 Tahun - Putri Octaviani (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This research discusses the effect of the storytelling method conducted by Sunday School teachers on the understanding of the Bible in children aged 3-6 years. The decline of attitude in early childhood is a cause for concern. This decline in attitude is caused by one of the problems, namely the lack of understanding of the Bible. The lack of teaching the Bible to children from an early age is a matter of concern. The storytelling method is a learning approach that prioritizes narratives or stories as the main medium in the religious learning process. Through interesting and interactive narratives, this method aims to increase children's understanding, engagement, creativity, and cognition, as well as forming positive attitudes towards religion and transferring moral values. This research uses a descriptive qualitative approach by collecting data from various literature sources related to the research topic. Data analysis was conducted systematically using a qualitative approach to generate new insights that can increase understanding of existing knowledge. The results showed that the storytelling method had a significant impact in several aspects. Firstly, it increases children's engagement in religious learning, allowing them to be actively involved and building a strong interest in the Bible. Second, it influences the growth of children's positive attitude towards religion, positively shaping their character and morality. Third, the storytelling method facilitates a deeper understanding of the Bible, allowing children to internalize the spiritual and moral values contained in the Bible stories. Fourth, it helps in the development of children's language and cognitive skills, enriching their learning experience. Fifth, the storytelling method facilitates the transfer of moral values, allowing children to understand moral concepts and develop attitudes that are in line with religious teachings. So, the storytelling method practiced by Sunday School teachers has a significant impact on the understanding of the Bible in children aged 3-6 years. This approach is not just about transferring knowledge, but also about shaping the child's character, morality and attitude towards religion. Therefore, it is important for religious educators to consider using the storytelling method in Bible learning for pre-school children in Sunday school.